Design of Lithium-Ion Battery Charger System with Automatic Voltage Regulator Feature - Shuhariman, Amirul Alif; Ponniran, Asmarashid (Evolution in Electrical and Electronic Engineering, 2023)
In industrial locations, the need for dc power is crucial in the twenty-first century. The majority of applications need the dc power supply for functioning. Effective DC power is capable of controlling electrical equipment properly. In this project, a rectifier and DC Buck converter are developed. The DC voltage is produced by the converter, which gets controlled by a microcontroller is represent the signal. PI controller is meant to alter the converter’s PI value in order to manage the output voltage of the buck converter. Using the MATLAB simulation application, the simulation circuit is created. Developing an experimental setup to validate simulation findings. Developing the buck converter circuit using MOSFET as the switching component. The microcontroller is utilized to run the PWM signal’s programmed PI controller. In this project, passive cell balancing is used to ensure that four cells are charged to the same proportion. The modeling and experimental findings indicate that the output voltage of the buck converter has been regulated with the PI value in the closed-loop system which provides the output voltage value of the maximum, mean, and minimum that is equivalent to 16.96 V, 16.82 V, and 16.66 V respectively. Thus, this proves that the research corresponding is successfully achieved because the output voltage value does not stray off from the desired value which equals 16.8 V.